2011
DOI: 10.1093/jac/dkr328
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of the rmtB gene carried on IncF and IncN plasmids among Enterobacteriaceae in a pig farm and its environment

Abstract: Both horizontal gene transfer and clonal spread could be responsible for the dissemination of the rmtB gene in the pig farm and its environment. To our knowledge, this study is the first report of rmtB-positive bacteria from farmland soils and indicates that these antibiotic-resistant bacteria and/or resistance genes could be acquired by humans through the food chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…Apart from the Bolivian region investigated in our work, consistent dissemination of CTX-M-65 has so far been limited to China and other Asiatic countries (i.e., Japan and Korea), where it is among the dominant CTX-M variants in enterobacteria of animal origin (36,(41)(42)(43)(44). The reasons accounting for the peculiar CTX-M-65 epidemiology, characterized by the distribution in two distant geographical areas, remain unknown.…”
Section: Discussionmentioning
confidence: 80%
“…Apart from the Bolivian region investigated in our work, consistent dissemination of CTX-M-65 has so far been limited to China and other Asiatic countries (i.e., Japan and Korea), where it is among the dominant CTX-M variants in enterobacteria of animal origin (36,(41)(42)(43)(44). The reasons accounting for the peculiar CTX-M-65 epidemiology, characterized by the distribution in two distant geographical areas, remain unknown.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, there is potential for horizontal transmission of plasmid-borne genes contributing to their distribution and abundance in soil (11). A number of previous studies have unambiguously shown that soils receiving animal manures or biosolids are enriched in antibiotic resistance genes (13,(16)(17)(18)(19)(20). A few studies have characterized gene abundance over time following application under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the majority of reports on dissemination of armA and rmtB to various Enterobacteriaceae species were focused on E. coli isolated from chickens and pigs (Yao et al, 2011; Yang Y. et al, 2015). Previous research has reported the occurrence of the ArmA methyltransferase in an ST11 clone of K. pneumoniae isolated from cats and dogs in Spain (Hidalgo et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%